The large magnetocaloric effect above room temperature in manganites (La1-xPrx)0.67Pb0.33MnO3 - Duong, Hanh Thi; Nguyen, Tho Duc; Nguyen, Chau; Nguyen, Luong Hoang (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts